2021
DOI: 10.1369/00221554211054585
|View full text |Cite
|
Sign up to set email alerts
|

Cell Biology Meets Cell Metabolism: Energy Production Is Similar in Stem Cells and in Cancer Stem Cells in Brain and Bone Marrow

Abstract: Energy production by means of ATP synthesis in cancer cells has been investigated frequently as a potential therapeutic target in this century. Both (an)aerobic glycolysis and oxidative phosphorylation (OXPHOS) have been studied. Here, we review recent literature on energy production in glioblastoma stem cells (GSCs) and leukemic stem cells (LSCs) versus their normal counterparts, neural stem cells (NSCs) and hematopoietic stem cells (HSCs), respectively. These two cancer stem cell types were compared because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 243 publications
(388 reference statements)
0
28
0
Order By: Relevance
“…In order to explain the lipid metabolism-associated metabolic switch, it has been speculated that proliferating NSCs activate lipogenesis in order to increase the amount of lipids available, that will later be use for plasma membrane synthesis (Knobloch, 2017). On the other hand, quiescent (non-proliferative) NSC use fatty acid oxidation to cover their energetic demands and maintain their stemness (van Noorden et al, 2022).…”
Section: Metabolic Requirements Of the Neural Stem Cell Nichementioning
confidence: 99%
“…In order to explain the lipid metabolism-associated metabolic switch, it has been speculated that proliferating NSCs activate lipogenesis in order to increase the amount of lipids available, that will later be use for plasma membrane synthesis (Knobloch, 2017). On the other hand, quiescent (non-proliferative) NSC use fatty acid oxidation to cover their energetic demands and maintain their stemness (van Noorden et al, 2022).…”
Section: Metabolic Requirements Of the Neural Stem Cell Nichementioning
confidence: 99%
“…[ 33 ] Our study revealed that compared to adherent cells, BCSCs have a higher FAO level, which is consistent with the fact that CSCs primarily rely on FAO‐mediated metabolic processes. [ 27,54 ] In addition, our data show that CD96 interacts with Src and facilitates phosphorylation of Stat3 in BCSCs, linking this interaction with the regulation of FAO in these cells. These results suggest that CD96‐Src regulates FAO in BCSCs via the Stat3 pathway.…”
Section: Discussionmentioning
confidence: 65%
“…The results demonstrated that modulation of PCAT‐1 influences the activity of PKM2, which subsequently affects the levels of β‐catenin, factor that is vital in the regulation of osteogenic differentiation 33 . In particular, MSCs that were subjected to vector PCAT‐1 treatment exhibited reduced concentrations of total β‐catenin 34 . This observation implies that PCAT‐1 regulates osteogenic differentiation by activating PKM2 and inhibiting the activities of β‐catenin.…”
Section: Discussionmentioning
confidence: 87%